Prevalence of musculoskeletal disorders, ergonomics risk assessment and implementation of participatory ergonomics program for pistachio farm workers - Hasheminejad, Naser; Choobineh, Alireza; Mostafavi, Reza; Tahernejad, Somayeh; Rostami, Matin (La Medicina del Lavoro, 2021)
Background and objectives: Pistachio farmers are exposed to a variety of risk factors for musculoskeletal disorders (MSDs). However, no study has been conducted to investigate MSDs in pistachio workers. Therefore, in the present study, besides investigating the prevalence of MSDs and their ergonomic risk factors, the participatory ergonomics (PE) method is used to provide an intervention program to reduce MSDs in this population in harvesting and processing pistachio. Methods: The present study was conducted in two phases. In the first phase 138 workers participated. The prevalence of MSDs was assessed with Nordic Musculoskeletal Questionnaire and the ergonomic risk factors was identified with ManTRA method. In the second phase PE was used to perform ergonomic interventions for reducing MSDs and the effect of the intervention was investigated. Sixty-four workers participated in the second phase (32 in the case group and 32 in the control group). Results: The highest prevalence of MSDs was in shoulders (63.7%), followed by the lower back (63%) and wrists/hands (52.1%). The comparison showed that after implementing the PE intervention program, the prevalence of MSDs in the intervention group was not significantly different from that in the control group. However, in the reassessment by the ManTRA method for five tasks that were identified as high risk in the first phase, a decrease in ManTRA final score was observed for all the five tasks. Conclusions: MSDs were prevalent in all body regions of workers. After implementing PE interventions exposure to ergonomic risk factors decreased.